CO2 storage site characterisation at the location of Harvey-3 well, Harvey, Western Australia - Urosevic, Milovan; Ziramov, Sasha; Pevzner, Roman; Tertyshnikov, Konstantin; Popik, D.; Van Gent, D. (2017)
The South West Hub is the first commercial scale CO2 capture and sequestration project in Australia. The project aims to capture CO2 from several significant polluters that are located around the town of Harvey, Western Australia. The potential CO2 reservoir is the prominent Lesueur sandstone formation while the Harvey-3 well is likely to be utilised for the first geo-sequestration test. Unfortunately, due to survey restrictions imposed in 2014, the area around the Harvey-3 well is void of seismic information. New developments have given rise to new seismic investigations which had to be designed in a unique manner due to limited access to the site. The data acquisition program is comprised of 2D surface and borehole surveys (550 OVSP points) and 3D surface and VSP surveys. Results will be discussed in detail.